2019
DOI: 10.2147/rrn.s208194
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pulmonary function and systolic blood pressure in very low birth weight infants at 34–36 weeks of corrected age</p>

Abstract: Purpose: Preterm infants are at increased risk of systemic hypertension compared to term infants. Bronchopulmonary dysplasia (BPD) has been shown to be associated with hypertension in preterm infants albeit with no causation reported. BPD is characterized by abnormal pulmonary function tests (PFTs), specifically elevated passive respiratory resistance (Rrs), decreased passive respiratory compliance (Crs), and decreased functional residual capacity (FRC). There have been no studies comparing PFTs in very low bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The length of the investigated period and the high number of blood pressure measurements make our study valuable in this eld. Several clinical studies have con rmed the increased risk of hypertension in BPD patients [5,[8][9][10][11][12][13]24], while other studies have not found a risk of high blood pressure in premature infants with BPD [6,7]. In addition to the different diagnostic criteria used for BPD and hypertension, this difference could be due to the various and short periods when the blood measurements were taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the investigated period and the high number of blood pressure measurements make our study valuable in this eld. Several clinical studies have con rmed the increased risk of hypertension in BPD patients [5,[8][9][10][11][12][13]24], while other studies have not found a risk of high blood pressure in premature infants with BPD [6,7]. In addition to the different diagnostic criteria used for BPD and hypertension, this difference could be due to the various and short periods when the blood measurements were taken.…”
Section: Discussionmentioning
confidence: 99%
“…BPD and the consequent hypertension can signi cantly affect premature infants' short-and long-term life outcomes. Despite several studies on this topic, there are unanswered questions on the development of blood pressure in premature infants with BPD [5][6][7][8][9][10][11][12][13]. Our study aims to investigate the blood pressure changes of premature BPD patients during the rst three months of life.…”
Section: Introductionmentioning
confidence: 99%
“…BPD and consequent hypertension can significantly affect premature infants' short-and long-term life outcomes. Despite several studies on this topic, there are unanswered questions regarding the blood pressure changes in premature infants with BPD [3][4][5][6][7][8][11][12][13][14]. Among these questions, the most important ones are the onset and frequency of hypertensive periods in BPD patients.…”
Section: Introductionmentioning
confidence: 99%